PENGEMBANGAN KEBIJAKAN TERHADAP HASIL EVALUASI IMPLEMENTASI PROGRAM DAN POLA SEBARAN KASUS KUSTA DI KOTA AMBON - Samsu, Semoel Leonard; Hafizurrachman, Muhammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Leprosy remains a public health problem in Ambon City, with major challenges in early detection, chemoprophylaxis coverage, and uneven case distribution. This study aims to develop policy recommendations based on the evaluation of leprosy program implementation and spatial distribution patterns of leprosy cases in Ambon City in 2024. This research employed a qualitative method using the CIPP evaluation model (Context, Input, Process, Product), combined with spatial analysis using GeoDa software and the K-Means Clustering technique. Data were collected through document review, in-depth interviews, field observations, and geospatial mapping. This study uses a qualitative method, with the CIPP (Context, Input, Process, Product) evaluation model, and spatial analysis using GeoDa software with the K-Means Clustering technique. Data were collected through document review, in-depth interviews, data observation, and geospatial mapping. Results: Shows that the context and input variables are in the fairly good category, but in the process variables there is a mismatch between the implementation of the intervention and operational standards, such as less than optimal close contact tracing. In the product variable, the success of the program implementation has not been in line with a significant decrease in cases. The results of triangulation show that data from interviews and observations are mutually reinforcing, while findings from documents at several points are not fully synchronized. Spatial analysis using K-Means Clusters groups the regions into five clusters; areas with high cases tend to be in remote areas and difficult to reach. This pattern indicates an uneven distribution of cases and the need for area-based interventions. The evaluation results indicate the need for improvements in process and outcome variables, including spatial distribution. The policies developed are directed at improving the reporting recording system, strengthening the capacity of health workers, optimizing close contact tracing and chemoprophylaxis, using spatial analysis to accelerate early detection, and reducing active transmission, especially in remote areas with high cases. The implementation of the leprosy program in Ambon City still faces significant challenges and requires a more integrated and area-based approach, based on the results of the evaluation and spatial mapping. ABSTRAKKusta masih menjadi masalah kesehatan di Kota Ambon dengan tantangan utama pada deteksi dini, cakupan kemoprofilaksis, dan distribusi kasus yang tidak merata. Penelitian ini bertujuan untuk mengembangkan kebijakan terhadap hasil evaluasi implementasi program kusta dan pola sebaran kasus kusta di Kota Ambon tahun 2024. Penelitian ini menggunakan metode kualitatif, dengan model evaluasi CIPP (Context, Input, Process, Product), serta analisis spasial menggunakan software GeoDa dengan teknik K-Means Clustering. Data dikumpulkan melalui telaah dokumen, wawancara mendalam, observasi data, dan pemetaan geospasial. Menunjukkan bahwa variabel konteks dan input berada dalam kategori cukup baik, namun pada variabel proses ditemukan ketidaksesuaian antara pelaksanaan intervensi dan standar operasional, seperti pelacakan kontak erat yang belum optimal. Pada variabel produk, keberhasilan pelaksanaan program belum sejalan dengan penurunan kasus secara signifikan. Hasil triangulasi menunjukkan bahwa data dari wawancara dan observasi saling menguatkan, sementara temuan dari dokumen pada beberapa poin tidak sepenuhnya sinkron. Analisis spasial menggunakan K-Means Clusters mengelompokkan wilayah menjadi lima klaster; daerah dengan kasus tinggi cenderung berada di wilayah pinggiran dan sulit dijangkau. Pola ini mengindikasikan distribusi kasus yang tidak merata dan perlunya intervensi berbasis wilayah. Hasil evaluasi menunjukkan perlunya perbaikan pada variabel proses dan hasil, termasuk distribusi spasial. Kebijakan yang dikembangkan diarahkan pada peningkatan sistem pencatatan pelaporan, penguatan kapasitas tenaga kesehatan, optimalisasi pelacakan kontak erat dan kemoprofilaksis, penggunaan analisis spasial dalam mempercepat deteksi dini, serta mengurangi penularan aktif, khususnya pada wilayah pinggiran dengan kasus tinggi. implementasi program kusta di Kota Ambon masih menghadapi tantangan signifikan dan membutuhkan pendekatan yang lebih terintegrasi dan berbasis wilayah, berdasarkan hasil evaluasi dan pemetaan spasial.